2006
DOI: 10.1293/tox.19.155
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocarcinogenesis by DDT in Rats

Abstract: DDT is known as a nongenotoxic hepatocarcinogen and has been shown to induce microsomal enzymes and GGT-positive foci and to inhibit gap junctional intercellular communication (GJIC) in the rodent liver. In consideration of these findings, we examined time-related changes in potential factors including hepatic enzyme induction, oxidative stress, cell proliferation, and GJIC in a 4-week and a 2-year feeding studies of p,p'-DDT with F344 rats. Consequently, hepatic microsomal P450 isozymes such as CYP2B1 and CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While previous studies have reported that continuous intrahepatic necroinflammatory changes were observed during the process of DEN initiated carcinogenesis, the pathogenetic importance of the inflammatory response has not been well defined (Matsuda et al, 2005) DDT may induce eosinophilic altered hepatocellular foci and promote the progression of preneoplastic into hepatocellular tumors. The production of oxidative stress which might be secondary to metabolic activation could be a key factor in hepatocarcinogenesis by DDT and play an important role in tumor promotion and progression (Harada et al, 2006).…”
Section: Hepatotoxicity: Effect Of Aqueous Extract On Alanine Transammentioning
confidence: 99%
“…While previous studies have reported that continuous intrahepatic necroinflammatory changes were observed during the process of DEN initiated carcinogenesis, the pathogenetic importance of the inflammatory response has not been well defined (Matsuda et al, 2005) DDT may induce eosinophilic altered hepatocellular foci and promote the progression of preneoplastic into hepatocellular tumors. The production of oxidative stress which might be secondary to metabolic activation could be a key factor in hepatocarcinogenesis by DDT and play an important role in tumor promotion and progression (Harada et al, 2006).…”
Section: Hepatotoxicity: Effect Of Aqueous Extract On Alanine Transammentioning
confidence: 99%
“…Here, 11 pesticides were detected [11], including the pesticide DDT (dichlorodiphenyltrichloroethane), its derivatives DDD (dichlorodiphenyldichloroethane) and DDE (diclhorodiphenyldichloroethylene)-pesticides that have been permanently banned since 2009 [14]. According to Faroon et al (2019) [15], DDT and its metabolites are responsible for several harmful effects, which include hepatotoxic and hepatocarcinogenesis [16,17], neurological and neurodevelopment effects [18,19], reproductive and development effects [20,21], obesogenic effect [22][23][24][25], and suppression/stimulation of different immune responses [26,27].…”
Section: Introductionmentioning
confidence: 99%